Comparison of the C‐MAC video laryngoscope with direct Macintosh laryngoscopy in the emergency department. (29th January 2015) - Vassiliadis, John; Tzannes, Alex; Hitos, Kerry; Brimble, Jessica; Fogg, Toby
Abstract: Objective: To investigate the first pass success rate, airway grade and complications in two tertiary EDs with the C‐MAC video laryngoscope (VL), when compared with standard direct laryngoscopy (DL). Methods: This was a retrospective analysis of prospectively collected data entered into an airway registry database in the EDs of Royal North Shore and St George Hospitals (SGH) over a 30 month period. Doctors had the choice of using either DL using a Macintosh or Miller blade or a C‐MAC VL for the intubation. Results: Six hundred and nineteen consecutive patients were recruited. There was no statistical difference between VL and DL in grade of view obtained, P = 0.526. Chance of intubation success increased by more than threefold by using a C‐MAC VL in the setting of a grade III/IV (total of 109) on DL (OR = 3.06; 95% CI: 1.52–6.17; P = 0.002). Conclusion: This is the first observational study of airway management comparing the C‐MAC VL with DL blades in an Australian ED population. Our findings revealed that although the C‐MAC VL overall did not provide an enhanced view of the larynx over the Macintosh DL, it was superior to DL when the grade was at least grade III. Currently we are unable to reliably predict the grade by any algorithm prior to intubation. Findings from this study suggest that the C‐MAC VL should be considered as the first line laryngoscope in all ED intubations not just the ones predicted to be difficult.